THE NECESSITY OF THE PAYMENT SYSTEM - Sadullaeva Mokhinur Aziz kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article discusses the main aspects of the payment system, its structure, and its impact on the economy. It analyzes the interrelationship between the payment system and inflation, the development features of this system in Uzbekistan, and its effect on the country's financial stability. The study is based on the works of scholars such as F.Mishkin, L.Lafontaine, J.Tobin, as well as Uzbek economists I.Abdullayev and Kh.Rakhmatov.